2018
DOI: 10.3389/fpubh.2018.00105
|View full text |Cite
|
Sign up to set email alerts
|

Persuasiveness of Statistics and Patients’ and Mothers’ Narratives in Human Papillomavirus Vaccine Recommendation Messages: A Randomized Controlled Study in Japan

Abstract: BackgroundThe human papillomavirus (HPV) vaccination percentage among age-eligible girls in Japan is only in the single digits. This signals the need for effective vaccine communication tactics. This study aimed to examine the influence of statistical data and narrative HPV vaccination recommendation massages on recipients’ vaccination intentions.MethodsThis randomized controlled study covered 1,432 mothers who had daughters aged 12–16 years. It compared message persuasiveness among four conditions: statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 54 publications
1
27
2
Order By: Relevance
“…Thus, the answer to our research question 2 was also "no". Our previous study showed that vaccination intention increased significantly directly after reading intervention materials, and that statistical messages plus a mother's narrative increased vaccination intention the most [9]. However, the present findings revealed that those effects wore off during the 4 months following intervention.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…Thus, the answer to our research question 2 was also "no". Our previous study showed that vaccination intention increased significantly directly after reading intervention materials, and that statistical messages plus a mother's narrative increased vaccination intention the most [9]. However, the present findings revealed that those effects wore off during the 4 months following intervention.…”
Section: Discussioncontrasting
confidence: 83%
“…This result indicated that exposure to messaging about efficacy and safety of HPV vaccine may increase vaccination intention of mothers with daughters directly after exposure to messaging, whether this includes only statistical messages, or narratives of experiences with cervical cancer in addition to statistical messages. Additionally, our previous study showed that the intention for the statistical messages plus mother's narrative was the highest among the intervention groups and was significantly higher than in the statistics-only group (p=0.040) [9]. This indicated that the narrative messages of a mother whose daughter experienced cervical cancer may be persuasive for audiences who are mothers with daughters.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations